The physiochemical properties and shelf‐life of orange‐fleshed sweet potato puree composite bread - Wanjuu, C.; Abong, G.O.; Mbogo, D.; Heck, S.; Low, Jan W.; Muzhingi, T. (Wiley, 2018)
Value addition of orange‐fleshed sweet potato (OFSP) increases diversified utilization of this crop, which is rich in provitamin A carotenoids. OFSP bread, in which 30%–45% of wheat flour is replaced with OFSP puree, has been successfully commercialized in Kenya. However, the effect of this substitution on the bread's physiochemical properties and its shelf‐life are currently unknown. This study was designed to determine the physiochemical properties and shelf‐life of OFSP puree‐wheat flour composite bread (30% puree), compared to standard, 100% wheat flour, bread. Freshly baked bread samples were stored at 7, 20, 25, and 30°C, and monitored for moisture content, water activity, color, texture, volume, carotenoids, and microbial load. The moisture content, β‐carotene content, and color of bread significantly decreased with increase in storage temperature and time (p < 0.05). Bread made with OFSP puree had a longer shelf‐life, showing spoilage on day six compared with the white bread, which spoiled on the fourth day. This is attributed to the significantly higher water activity in white bread than in the OFSP bread. The substitution of wheat with OFSP puree resulted in reduced extensibility of gluten, thus, specific volume of white bread was significantly (p < 0.05) higher than that in OFSP puree bread. Refrigeration increased crumb firmness, chewiness and cohesiveness in both types of bread. In conclusion, OFSP puree increases the water binding capacity of the bread, which reduces water activity and increases its shelf‐life.